Role of the H-2 complex in the induction of T cell tolerance to self minor histocompatibility antigens (The Rockefeller University Press, 1983)
The present study has utilized cytotoxic T lymphocyte (CTL) responses specific for minor histocompatibility (minor H) antigens as an experimental approach to determining whether recognition of self MHC determinants is involved in the induction of T cell tolerance to self antigens. It was observed that C3H.SW splenic T cells from C3H.SW leads to B10 X B10.BR radiation bone marrow chimeras contained CTL precursors (pCTL) reactive against self C3H minor H antigens + H-2k but were tolerant to self C3H minor H antigens + H-2b. Precursor CTL with the reciprocal reactivity pattern were observed for C3H leads to B10 X B10.BR chimeras. In addition, it was observed that C3H.SW thymocytes from C3H.SW leads to B10 X B10.BR chimeras could generate minor H- specific CTL responses and were reactive against self C3H minor H antigens + H-2k, but were tolerant to self C3H minor H antigens + H-2b. Thus, the present study demonstrates that for peripheral and intrathymic T cell populations at least a component of T cell tolerance to self antigens is restricted by products of the MHC.